2010
DOI: 10.1017/s0033291710000553
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and moderators of time to remission of major depression with interpersonal psychotherapy and SSRI pharmacotherapy

Abstract: Background Although many studies suggest that, on average, depression-specific psychotherapy and antidepressant pharmacotherapy are efficacious, we know relatively little about which patients are more likely to respond to one versus the other. We sought to determine whether measures of spectrum psychopathology are useful in deciding which patients with unipolar depression should receive pharmacotherapy vs. depression-specific psychotherapy. Methods 318 adult outpatients with major depression were randomly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 31 publications
5
96
0
Order By: Relevance
“…Another possible contributor is the nature of our study protocol, including relatively frequent visits to the clinic (once a week during the acute phase, with the possibility of more frequent visits when necessary), the involvement of family members and friends through inclusion in patients' initial evaluation and in a psychoeducational workshop on depression and the goals of the study, and the availability of an emergency phone service that gave each patient the possibility of speaking with a study clinician (most often his/her own treating clinician) 24 hr a day. [26] Regarding the demographic and clinical predictors of relapse, we found that older age, higher severity of depression at baseline, and residual symptoms of depressive mood spectrum conferred higher risk during the continuation phase. Our results are consistent with evidence from the literature suggesting that residual symptoms together with symptom severity are significant predictors of relapse.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Another possible contributor is the nature of our study protocol, including relatively frequent visits to the clinic (once a week during the acute phase, with the possibility of more frequent visits when necessary), the involvement of family members and friends through inclusion in patients' initial evaluation and in a psychoeducational workshop on depression and the goals of the study, and the availability of an emergency phone service that gave each patient the possibility of speaking with a study clinician (most often his/her own treating clinician) 24 hr a day. [26] Regarding the demographic and clinical predictors of relapse, we found that older age, higher severity of depression at baseline, and residual symptoms of depressive mood spectrum conferred higher risk during the continuation phase. Our results are consistent with evidence from the literature suggesting that residual symptoms together with symptom severity are significant predictors of relapse.…”
Section: Discussionmentioning
confidence: 73%
“…[26] The study was approved by the Institutional Review Board of the University of Pittsburgh and the Ethics Committee of the Azienda Ospedaliero-Universitaria of Pisa. All participants provided written informed consent.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Baseline depression severity has sometimes been noted as EM in the choice of treatments with psychotherapy, pharmacotherapy, or their combination [48, 49] but not always [50]. Anxiety or some related characteristics have also been suggested to moderate the treatment effects in several studies [51, 52] but there are far fewer studies on the impact of anxiety in the treatment of depression. Prior drug treatment was found to be an EM in another study [53].…”
Section: Discussionmentioning
confidence: 99%
“…1. Thirty-five studies met inclusion criteria [2][3][4]5,6,8,[15][16][17][18]20,21,24,27,31,33,34,[40][41][42][43]45,46,[50][51][52][53][56][57][58][60][61][62]65,66]. Fig.…”
Section: Selection and Inclusion Of Studiesmentioning
confidence: 99%